Analisis Komponen Darah dari Berbagai Fase Reproduksi Induk Domba (Ovis aries) Sapudi - Anggita, Arnes; Mudawamah, Mudawamah; Sumartono, Sumartono (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Indonesia has several types of local sheep, including Sapudi sheep. In increasing sheep production and population, it is necessary to pay attention to the reproductive system. The metabolism and physiology of pregnant sheep will experience changes which cause blood components to also change. The research sample was 20 Sapudi ewes from UPT. Livestock Breeding and Forage in Jember. Mother sheep were divided into 5 groups according to their reproductive phase, namely non-pregnant mothers, early pregnancy, mid-pregnancy, late pregnancy, and lactating mothers. The research variables are blood components which include erythrocytes, leukocytes, hemoglobin and hematocrit. The research method is quantitative descriptive which is analyzed using one-way variance, and if it is significantly different, the Duncan test is continued. The results of this study showed significant differences (p<0.05) in hemoglobin, while there were no significant differences in erythrocytes, leukocytes and hematocrit (p>0.05). The average hemoglobin value in the five reproductive phases is between 7.65-10.50 g/dL, erythrocytes 5.78-6.95 106/mm3, leukocytes 8.05-13.71 106/ÂµL, and hematocrit 24.35 -29.70%.